Intervention planning for the REDUCE maintenance intervention: a digital intervention to reduce re-ulceration risk among patients with a history of diabetic foot ulcers - Greenwell, Kate; Sivyer, Katy; Vedhara, Kavita; Yardley, Lucy; Game, Frances; Chalder, Trudie; Richards, Gayle; Drake, Nikki; Gray, Katie; Weinman, John; Bradbury, Katherine (BMJ Publishing Group Ltd, 2018)
Objectives: To develop a comprehensive intervention plan for the REDUCE maintenance intervention to support people who have had diabetic foot ulcers (DFUs) to sustain behaviours that reduce re-ulceration risk.